Magnetic resonance imaging of temporomandibular joint disc abnormalities: A pictorial essay - Galal Omami (Wolters Kluwer Medknow Publications, 2013)
Internal derangement is the most common pathological condition affecting the temporomandibular joint (TMJ). Magnetic resonance imaging (MRI) of TMJ is principally directed toward assessment of the soft-tissue abnormalities in terms of internal derangement. This pedagogical article describes anatomy and biomechanics and provides a pictorial overview of the MRI findings of the disc abnormalities of TMJ.